Cortical Granule Distribution and Expression Pattern of Genes Regulating Cellular Component Size, Morphogenesis, and Potential to Differentiation are Related to Oocyte Developmental Competence and Maturational Capacity In Vivo and In Vitro - Kulus, Magdalena; Kranc, Wiesława; Jeseta, Michal; Sujka-Kordowska, Patrycja; Konwerska, Aneta; Ciesiółka, Sylwia; Celichowski, Piotr; Moncrieff, Lisa; Kocherova, Ievgeniia; Józkowiak, Małgorzata; Kulus, Jakub; Wieczorkiewicz, Maria; et al. (Genes, 2020)
Polyspermia is an adverse phenomenon during mammalian fertilization when more than one sperm fuses with a single oocyte. The egg cell is prepared to prevent polyspermia by, among other ways, producing cortical granules (CGs), which are specialized intracellular structures containing enzymes that aim to harden the zona pellucida and block the fusion of subsequent sperm. This work focused on exploring the expression profile of genes that may be associated with cortical reactions, and evaluated the distribution of CGs in immature oocytes and the peripheral density of CGs in mature oocytes. Oocytes were isolated and then processed for in vitro maturation (IVM). Transcriptomic analysis of genes belonging to five ontological groups has been conducted. Six genes showed increased expression after IVM (ARHGEF2, MAP1B, CXCL12, FN1, DAB2, and SOX9), while the majority of genes decreased expression after IVM. Using CG distribution analysis in immature oocytes, movement towards the cortical zone of the oocyte during meiotic competence acquisition was observed. CGs peripheral density decreased with the rise in meiotic competence during the IVM process. The current results reveal important new insights into the in vitro maturation of oocytes. Our results may serve as a basis for further studies to investigate the cortical reaction of oocytes.
Keywords: In Vitro Oocyte Maturation Techniques; Animals; Oocytes; transkriptom; Cell Differentiation; buněčná diferenciace; Cells, Cultured; Female; zvířata; Transcriptome; IVM techniky; oocyty; prasata; Cytoplasmic Granules; Swine; cytoplazmatická granula; ženské pohlaví; kultivované buňky